2003
DOI: 10.1111/j.1945-5100.2003.tb00001.x
|View full text |Cite
|
Sign up to set email alerts
|

The shape and appearance of craters formed by oblique impact on the Moon and Venus

Abstract: Abstract-We surveyed the impact crater populations of Venus and the Moon, dry targets with and without an atmosphere, to characterize how the 3-dimensional shape of a crater and the appearance of the ejecta blanket varies with impact angle. An empirical estimate of the impact angle below which particular phenomena occur was inferred from the cumulative percentage of impact craters exhibiting different traits. The results of the surveys were mostly consistent with predictions from experimental work. Assuming a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
66
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 27 publications
7
66
1
Order By: Relevance
“…As impact angle decreases on both planets, first the uprange and then the downrange rim go to zero elevation, while the crossrange rim elevation remains unchanged. The Herrick and Forsberg-Taylor (2003) surveys are consistent with the Bottke et al (2000) results for grazing impacts, but the number of craters surveyed are far fewer because Herrick and ForsbergTaylor (2003) considered only well-preserved craters. At small crater diameters on Venus (<15 km), meteoroid breakup and dispersal becomes a significant fraction of crater diameter (Herrick and Phillips 1994), and a variety of crater shapes and planforms can be observed that are consistent with clustered, oblique impact experiments (Schultz and Gault 1985).…”
Section: Introductionsupporting
confidence: 65%
See 4 more Smart Citations
“…As impact angle decreases on both planets, first the uprange and then the downrange rim go to zero elevation, while the crossrange rim elevation remains unchanged. The Herrick and Forsberg-Taylor (2003) surveys are consistent with the Bottke et al (2000) results for grazing impacts, but the number of craters surveyed are far fewer because Herrick and ForsbergTaylor (2003) considered only well-preserved craters. At small crater diameters on Venus (<15 km), meteoroid breakup and dispersal becomes a significant fraction of crater diameter (Herrick and Phillips 1994), and a variety of crater shapes and planforms can be observed that are consistent with clustered, oblique impact experiments (Schultz and Gault 1985).…”
Section: Introductionsupporting
confidence: 65%
“…In this work, we use a methodology similar to that used in Herrick and Forsberg-Taylor (2003). We surveyed a large number of craters within a given area in a manner that allowed us to attribute the variations in crater appearance to impact angle.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations